Designing Knowledge Management System to Improve Employee Competencies at Saka Grou" - Loudia Anggita, Ingelora; Ghazali, Achmad (The Indonesian Journal of Business Administration, 2019)
Abstract. In 2014, when PT Saka Energi Indonesia (SEI) acquired HESS; oil and gas companies from the United States, Saka changed the organization including in terms of human resource management. It was found that some regions still had gaps, namely: career management and competence, remuneration, learning and performance. At present, knowledge is seen as a strategic resource whose role is very important for the Company to have a competitive advantage. One of the Company's successes in generating competitive advantages depends on the Company's ability to manage, obtain and assimilate knowledge. Without realizing it, knowledge management has been carried out by workers as individuals or individuals. This research was made to be able to determine the extent to which the understanding and interest of Saka workers has a knowledge management system to be applied in the Company using qualitative and quantitative methods. Referring to the 4 (four) perspectives in the SECI Nonaka model: people, processes, technology and governance are expected to be able to answer the questions in this study. The results of this study show that SAKA workers have carried out knowledge management in their daily work and they support if this is legalized.Keywords: Knowledge Management, Knowledge & Information Management, Energy Sector, Oil and Gas Industry, Saka Group